PENGARUH EFEKTIVITAS PENGGUNAAN SISTEM PERPAJAKAN ONLINE E-TAX PADA KEPATUHAN PELAPORAN PAJAK DAERAH KABUPATEN BADUNG - Ni Made Estiyanti; I Putu Rawindra Wikantona; I Gede Putu Krisna Juliharta (Journal of Applied Management and Accounting Science, 2019)
This study aims to analyze the effectiveness of the use of the taxation system e-tax online in compliance with the Badung Regency tax reporting. Sampling is done by method random sampling. The data collection method was carried out by distributing questionnaires to 143 taxpayers consisting of hotel, restaurant, parking and entertainment taxpayers. The analysis technique used is a simple linear regression analysis technique that is preceded by a classic assumption test and processed using the program SPSS version 16.0. The results of this study indicate an increase in the effectiveness of the use of the taxation system e-tax online will be followed by an increase in compliance with the tax reporting in the Badung Regency. And there is a significant influence on the effectiveness of the use of the taxation system e-tax online in the compliance of the Badung district tax reporting.